Evaluation of performance as a tool for the analysis of human capital - Montoya, César Alveiro (Scientific Journal Visión de Futuro, 2008)
This work tries to show a scheme of performance evaluation for employees, considering that, is constituted nowadays in the organizations as an essential tool for those who have the responsibility of managing human talent. Due to the aforesaid, one must keep in mind the aspects on behalf of those responsible of the performance, within the organizations and thus to be able to give the importance to the innumerous elements that constitute themselves as an essential part, when defining the aspects or key points for the development of the evaluation.